Mechanism and treatment of intracerebral hemorrhage focus on mitochondrial permeability transition pore - Cong, Jing; Li, Jing-Yi; Zou, Wei (Frontiers in Molecular Neuroscience, 2024)
Intracerebral hemorrhage (ICH) is the second most common subtype of stroke, characterized by high mortality and a poor prognosis. Despite various treatment methods, there has been limited improvement in the prognosis of ICH over the past decades. Therefore, it is imperative to identify a feasible treatment strategy for ICH. Mitochondria are organelles present in most eukaryotic cells and serve as the primary sites for aerobic respiration and energy production. Under unfavorable cellular conditions, mitochondria can induce changes in permeability through the opening of the mitochondrial permeability transition pore (mPTP), ultimately leading to mitochondrial dysfunction and contributing to various diseases. Recent studies have demonstrated that mPTP plays a role in the pathological processes associated with several neurodegenerative diseases including Parkinson’s disease, Alzheimer’s disease, Huntington’s disease, ischemic stroke and ischemia-reperfusion injury, among others. However, there is limited research on mPTP involvement specifically in ICH. Therefore, this study comprehensively examines the pathological processes associated with mPTP in terms of oxidative stress, apoptosis, necrosis, autophagy, ferroptosis, and other related mechanisms to elucidate the potential mechanism underlying mPTP involvement in ICH. This research aims to provide novel insights for the treatment of secondary injury after ICH.